Neurite growth acceleration of adult Dorsal Root Ganglion neurons illuminated by low‐level Light Emitting Diode light at 645 nm. Issue 6 (30th July 2014) - Burland, Marion; Paris, Lambert; Quintana, Patrice; Bec, Jean‐Michel; Diouloufet, Lucie; Sar, Chamroeun; Boukhaddaoui, Hassan; Charlot, Benoit; Braga Silva, Jefferson; Chammas, Michel; Sieso, Victor; Valmier, Jean; et al.
<x xml:space="preserve">Abstract</x> The effect of a 645 nm Light Emitting Diode (LED) light irradiation on the neurite growth velocity of adult Dorsal Root Ganglion (DRG) neurons with peripheral axon injury 4–10 days before plating and without previous injury was investigated. The real amount of light reaching the neurons was calculated by taking into account the optical characteristics of the light source and of media in the light path. The knowledge of these parameters is essential to be able to compare results of the literature and a way to reduce inconsistencies. We found that 4 min irradiation of a mean irradiance of 11.3 mW/cm2 (corresponding to an actual irradiance reaching the neurons of 83 mW/cm2) induced a 1.6‐fold neurite growth acceleration on non‐injured neurons and on axotomized neurons. Although the axotomized neurons were naturally already in a rapid regeneration process, an enhancement was found to occur while irradiating with the LED light, which may be promising for therapy applications. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> Dorsal Root Ganglion neurons (A) without previous injury and (B) subjected to a conditioning injury. </boxed-text>